Eco Enzyme Training as an Alternative for Vegetable Organic Waste Processing in Karangsari Village - Sativa, Rima Dewi Oryza (Kontibusi: Jurnal Kontribusi Kepada Masyarakat, 2021)
The Real Work Lecture with the theme "Towards Prosperity and Health in the New Normal Era" is a community service, namely the role of students to seek counseling and training on making eco-enzymes that are beneficial to the community in Karangsari Village, which still requires a lot of support from various parties, especially in Covid-19 prevention efforts. Eco enzyme is the result of a simple fermentation of vegetable waste with the addition of molasses and water. Eco Enzyme can be used as a disinfectant and hand sanitizer, fertilizing soil and plants. In addition, eco enzyme also has economic value that we can use to minimize organic waste to be processed. This activity aims to, (1) provide and introduce how to process household organic waste vegetables into eco-enzymes; (2) raise public awareness through processing household waste into goods of economic value. This training activity is the result of community service innovation creating UNISBA collaboration with the people of Blitar City.